Isaac of Stella's Sermons for the Feast of All Saints - Troupeau, Jean (Cistercian studies quarterly, 2019)
The article offers information on the Sermons for the Feast of All Saints by Isaac of Stella. Topics discussed include commentary on the Sermon on the Mount; explanation of the parable of the Good Samaritan; and development of Western exegesis on this text of the beatitudes such as Saint Augustine's intuitions and the teaching of the school of Saint-Victor.